From Tribulations to Appreciation: Experiencing Adversity in the Past Predicts Greater Savoring in the Present. (July 2014) - Croft, Alyssa; Dunn, Elizabeth W.; Quoidbach, Jordi
Can experiencing adversity enhance people's appreciation for life's small pleasures? To examine this question, we asked nearly 15, 000 adults to complete a vignette-based measure of savoring. In addition, we presented participants with a checklist of adverse events (e.g., divorce, death of a loved one) and asked them to indicate whether they had experienced any of these events and, if so, to specify whether they felt they had emotionally dealt with the negative event or were still struggling with it. Although people who were currently struggling with adversity reported a diminished proclivity for savoring positive events, individuals who had dealt with more adversity in the past reported an elevated capacity for savoring. Thus, the worst experiences in life may come with an eventual upside, by promoting the ability to appreciate life's small pleasures.